Prevalence of ENT diseases in Chitradurga district of Karnataka, India - Singh, Amardeep; K., Manjunath; S. V., Manjunatha Rao; S., Akash Aradhya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Study was conducted to observe the magnitude of ENT morbidity in the predominantly rural district of Chitradurga, Karnataka. Methods: It was a retrospective study based on medical records of the patients attending OPD of Otorhino-laryngology department in a tertiary care hospital. Retrieved data was tabulated in terms of frequency and percentage to assess the prevalence of ENT diseases in this region. Results: Study revealed high prevalence of ear diseases (40.4%) followed by throat problems (28.5%). Among ear group, majority of patients (19.7%) had otitis media. In throat region, there was high prevalence of pharyngitis (12.8%) and tonsillitis (8.0%). Nasal diseases reflected allergic rhinitis (7.0%) and symptomatic DNS (6.5%) as the major contributors to ENT pathologies. Conclusions: Results of the present study reveal that ear and throat diseases form the largest component of ENT problems. Most of these are infectious and preventable. Health education of general population will play a major role in curtailing the related morbidity.